Developing Infrastructure to Support Closer Collaboration of Aggregators with Open Repositories - Pontika, Nancy; Knoth, Petr; Cancellieri, Matteo; Pearce, Samuel (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
The amount of open access content stored in repositories has increased dramatically, which has created new technical and organisational challenges for bringing this content together. The COnnecting REpositories (CORE) project has been dealing with these challenges by aggregating and enriching content from hundreds of open access repositories, increasing the discoverability and reusability of millions of open access manuscripts. As repository managers and library directors often wish to know the details of the content harvested from their repositories and keep a certain level of control over it, CORE is now facing the challenge of how to enable content providers to manage their content in the aggregation and control the harvesting process. In order to improve the quality and transparency of the aggregation process and create a two-way collaboration between the CORE project and the content providers, we propose the CORE Dashboard.